FMR Study of ZnFe2O4 Thin Films in varied Growth Environments - Singh N.; Annadi A.; Rastogi A.; Kumar N.; Sahu B.; Bhoi B.; Bohra M. (My University, 2025)
The quest for improved ferrimagnetic insulators has garnered significant research interest for spintronic devices due to their low damping constants. In this work, we investigated the growth and frequency - dependent microwave properties of sputtered ZnFe2 O4 thin films grown under different gaseous environments and substrate temperatures (Ts). While an argon environment promotes (111) textured ZnFe2 O4 growth at intermediate Ts, an oxygen environment produces amorphous ZnFe2 O4 regardless of Ts. A reasonably high effective magnetization, 4πMeff=~ 0.3-3.7 kG and effective anisotropy were estimated by ferromagnetic resonance (FMR) using Kittel equations in both gaseous environments at intermediate Ts. The lowest Gilbert damping constant (α ≈ 4.18 × 10-3) and inhomogeneous broadening (ΔH0=318 Oe) were observed at the highest TS in the argon environment. Landau-Lifshitz damping plus inhomogeneous broadening alone cannot describe the damping in all ZnFe2 O4 thin films; a low-field-loss effect has to be considered to describe the entire frequency dependence of the linewidth. IEEE